Sabre-Rattling in the Persian Gulf: Legal and military aspects of the ideological confrontation between Iran and the United States - Walter Posch; Sascha Albrecht (Stiftung Wissenschaft und Politik (SWP), 2012)
When Iranian generals threatened in January 2012 to avenge any attack on the Islamic Republic by blocking the Strait of Hormuz, Barack Obama responded promptly and robustly. In a message addressed personally to Iran's Supreme Leader, the US President cautioned that »closing the Strait of Hormuz is our red line«. To underline its seriousness, the warning was communicated to Supreme Leader Seyyed Ali Khamenei via several channels simultaneously. The Iranian reaction was reserved: they would study the message but generally speaking Obama had said nothing new about the American-Iranian relationship. To the extent that relations have been characterised by reciprocal mistrust since 1979, that is certainly true. With a lack of functioning communication channels between the two countries, the resulting acute tensions are bound to come to a head at regular intervals
Keywords: 320